Can You Only Diagnose What You Know? The Relation Between Teachers’ Self-Regulation of Learning Concepts and Their Assessment of Students’ Self-Regulation - Dignath, Charlotte; Sprenger, Lara (Frontiers in Education, 2020)
Self-regulation of learning (SRL) positively affects achievement and motivation. Therefore, teachers are supposed to foster students‘ SRL by providing them with strategies. However, two preconditions have to be met: teachers need to diagnose their students‘ SRL to take instructional decisions about promoting SRL. To this end, teachers need knowledge about SRL to know what to diagnose. Only little research has investigated teachers’ knowledge about SRL and its assessment yet. Thus, the aim of this study was to identify teachers’ conceptions about SRL, to investigate their ideas about how to diagnose their students’ SRL, and to test relationships between both. To this end, we developed two systematic coding schemes to analyze the conceptions about SRL and the ideas about assessing SRL in the classroom among a sample of 205 teachers. The coding schemes for teachers’ open answers were developed based on models about SRL and were extended by deriving codes from the empirical data, and produced satisfying interrater reliability (conceptions about SRL: κ= .85, SE = .03; ideas about assessing SRL: κ= .63, SE = .05). The results showed that many teachers did not refer to any regulation procedure at all and described SRL mainly as student autonomy and self-directedness. Only few teachers had a comprehensive conception of the entire SRL cycle. We identified three patterns of teachers’ conceptualizations of SRL: a motivation-oriented, an autonomy-oriented, and a regulation-oriented conceptualization of SRL. Regarding teachers’ ideas about assessing their students’ SRL, teachers mainly focused on cues that are not diagnostic of SRL. Yet, many teachers knew about portfolios to register SRL among students. Finally, our results suggest that, partly, teachers’ ideas about assessing SRL varied as a function of their SRL concept: teachers with an autonomy-oriented conceptualization of SRL were more likely to use cues that are not diagnostic of SRL, such as unsystematic observation or off-task behavior. The results provide insights into teachers‘ conceptions of SRL and of its assessment. Implications for future research in the field of SRL will be drawn; in particular, about how to support teachers in diagnosing and fostering SR among their students.